Reading Families : Women's Literate Practice in Late Medieval England - Krug, Rebecca (Book collections on Project MUSE., 2002)
"Reading Families looks at the literate practice of two individual women, Margaret Paston and Margaret Beaufort, and of two communities in which women were central, the Norwich Lollards and the Bridgettines at Syon Abbey. The book begins with Paston's letters, which were written at her husband's request, and ends with devotional texts that describe the spiritual daughterhood of the Bridgettine readers."--Jacket.